Microstructural Characteristics and Mechanical Properties of Repaired Titanium Alloy Blade by Arc Additive Manufacturing Process. Issue 11 (8th July 2020) - Liu, Yibo; Jin, Peng; Li, Junzhao; Lin, Tong; Li, Fuxiang; Hou, Shaojun; Sun, Qingjie; Feng, Jicai
Abstract : To improve repair efficiency and achieve a high‐quality repair layer, wire and arc additive manufacturing process is used in this study to repair missing‐angle Ti‐6Al‐4V blade. The deposition layer with a mixed equiaxed β and columnar grain can be obtained by optimizing the deposition speed and single layer height. According to the characteristics of β grain, the typically repaired thin‐walled part is divided into four representative areas, including heat affected zone (HAZ), bottom layer, middle layer, and top layer. The bottom layer consists of coarsely near‐equiaxed β grains with martensite α′ and basket‐weave structure, and the columnar β grains grow perpendicularly from middle layer to top layer. The heat accumulation in HAZ continues to increase which resulted in a certain degree of cooling rate reduction, resulting in the martensite α′ decomposed to α dots and rods in HAZ near the layer band. The fine near‐equiaxed β grains (78 ± 28 μm), martensite α′ structure, and fine lamellar α structure are presented in HAZ, causing the fracture transition from the HAZ to bottom region. The characteristic of ductile rupture is observed in repaired thin‐wall, the maximum tensile strength is 991 MPa, and the elongation reaches about 10%. Abstract : The repaired Ti‐6Al‐4V blade with excellent properties is successfully obtained by using the arc + wire additive manufacturing process. The strategy of increasing the layer height and deposition rate is adopted to promote the columnar to equiaxed transformation. A fast cooling strategy is adopted to promote martensite α′ decomposed to α dots and rods in heat affected zone (HAZ).